2016
DOI: 10.5430/ijh.v3n1p17
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Reproductive Health indicators in Ethiopia: 2000-2014

Abstract: Introduction: The Millennium Development Goals include a focus on Reproductive Health (RH) indicators which are of substantial importance in low and middle income countries. However, little has been reported of the time-trend in these indicators in Ethiopia. This study aims to describe trends in RH indicators in Ethiopia from 2000-2014. Methods: This study is a time-trend analysis of RH indicators. We used 15-years of RH indicator data sourced mainly from Federal Ministry of Health and Demographic and Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…In our country Ethiopia, trends of reproductive health indicators from 2000-2014 showed that even though there is a significant improvement of maternal health care services utilization, the gap in the continuum of maternal health care services remains remarkably high [8]. According to Ethiopia Demographic and Health Survey(EDHS) 2016 report, out ofallreproductive-aged women, 62% received antenatal care (ANC) and 28% had skilled delivery assistance, among women, gave birth in the 2 years before the survey, 17% had a postnatal check [9].This showed that there is a significant drop out through maternity continuum of care and still little progress has been made in closing the gap between the level of maternal health care services.…”
Section: Introductionmentioning
confidence: 96%
“…In our country Ethiopia, trends of reproductive health indicators from 2000-2014 showed that even though there is a significant improvement of maternal health care services utilization, the gap in the continuum of maternal health care services remains remarkably high [8]. According to Ethiopia Demographic and Health Survey(EDHS) 2016 report, out ofallreproductive-aged women, 62% received antenatal care (ANC) and 28% had skilled delivery assistance, among women, gave birth in the 2 years before the survey, 17% had a postnatal check [9].This showed that there is a significant drop out through maternity continuum of care and still little progress has been made in closing the gap between the level of maternal health care services.…”
Section: Introductionmentioning
confidence: 96%
“…Sub-Saharan Africa shared the highest burden, accounting for almost half (48.3%) of all maternal deaths globally. Maternal mortality in Ethiopia remains high with a ratio of 497 deaths per 100,000 live births [4,7,8]. The 2015 MMR estimate of the country was 410 per 100,000 live births compared to 373, 338, and 280 in Rwanda, Kenya, and Uganda, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…The 2015 MMR estimate of the country was 410 per 100,000 live births compared to 373, 338, and 280 in Rwanda, Kenya, and Uganda, respectively [5]. The country reported the largest maternal mortality ratio from all causes for total world deaths [7,8] and did not achieve the goal of driving down maternal deaths to 267 per 100,000 by 2015 [9]. The high maternal death rate was primarily attributed to underutilization of antenatal clinics [1015] and institutional delivery [1622].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations